Theoretical insights into the excited-state intramolecular proton transfer (ESIPT) mechanism in a series of amino-type hydrogen-bonding dye molecules bearing the 10-aminobenzo[h]quinoline chromophore. (June 2017) - Zhu, Qiuling; Wen, Keke; Feng, Songyan; Wu, Wenpeng; An, Beibei; Yuan, Huijuan; Guo, Xugeng; Zhang, Jinglai
Abstract: Structures of a series of 10-aminobenzo[h]quinoline (ABQ ) derivatives in their ground states and first excited singlet states were optimized with density functional theory (DFT) and time-dependent density functional theory (TD-DFT) approaches. Their electronic absorption spectra and fluorescence emission spectra were simulated on the basis of the calculations on the vertical excitation and emission energies, which agree very well with the corresponding experimental spectra. The potential energy curves of their ground state and first excited singlet state were calculated by TD-DFT to elucidate the mechanisms of the excited-state intramolecular proton transfer (ESIPT) processes. It reveals that all the systems considered here can undergo a fast or even ultrafast ESIPT reaction, giving rise to the single fluorescence emission from their tautomer forms, as observed experimentally. Graphical abstract: Highlights: A stronger intramolecular hydrogen-bond leads to a lower energy barrier in the ESIPT reaction. The absorption and fluorescence properties of five amino-type hydrogen-bonding dye molecules are calculated. A new ESIPT dye molecule is theoretically designed.